1992
DOI: 10.1136/hrt.68.10.425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing heart rate on Doppler indices of left ventricular performance in healthy men

Abstract: Objective-To investigate the effects of heart rate on the Doppler measurements of left ventricular function and to determine the normal pattern of rate dependency.Setting--University hospital specialising in internal medicine.Participants-14 healthy male volunteers 10 of whom were studied.Intervention: Transoesophageal atrial pacing.Main outcome measures-At paced rates of 70, 80, and 90 ppm the ratio of early to late peak transmitral flow velocity (EIA) was 1P97 (0-28), 1'49 (0-21), and 0 95 (0 11) respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…42,43 With increasing heart rate, the diastolic filling pattern changes in favor of atrial contribution, together with a decrease of the velocity area of the early diastolic filling time and a decrease of the deceleration time, resulting in a lower ratio of the early to late peak filling rates and a lower ratio of early to late filling volumes. [44][45][46] Our study found a significantly higher ratio of peak early to atrial filling volumes in cyclists compared with control subjects, corresponding to slightly altered LV diastolic properties in cyclists. However, after correction for age and heart rate, the cyclists demonstrated a normal diastolic filling pattern, with no significant differences in parameters such as peak early filling rate, peak atrial filling rate, early filling volume, atrial filling volume, ratio of early to atrial filling volumes, mean acceleration gradient of early filling, mean deceleration gradient of early filling, mean acceleration gradient of atrial filling, and atrial filling fraction.…”
Section: Diastolic Functionmentioning
confidence: 47%
“…42,43 With increasing heart rate, the diastolic filling pattern changes in favor of atrial contribution, together with a decrease of the velocity area of the early diastolic filling time and a decrease of the deceleration time, resulting in a lower ratio of the early to late peak filling rates and a lower ratio of early to late filling volumes. [44][45][46] Our study found a significantly higher ratio of peak early to atrial filling volumes in cyclists compared with control subjects, corresponding to slightly altered LV diastolic properties in cyclists. However, after correction for age and heart rate, the cyclists demonstrated a normal diastolic filling pattern, with no significant differences in parameters such as peak early filling rate, peak atrial filling rate, early filling volume, atrial filling volume, ratio of early to atrial filling volumes, mean acceleration gradient of early filling, mean deceleration gradient of early filling, mean acceleration gradient of atrial filling, and atrial filling fraction.…”
Section: Diastolic Functionmentioning
confidence: 47%
“…Furthermore, the well-known positive chronotropic effect of levosimendan 1 also might contribute to the decrease in E/A ratio seen in patients with heart failure because a negative linear relationship between heart rate and the E/A ratio has been described. 11,12 In a recent Doppler echocardiographic study of patients with acute myocardial infarction, it was shown that 24-hour administration of levosimendan after primary angioplasty decreased the IVRT, which was interpreted as an improvement in diastolic function. 9 The E/A ratio increased to the same extent in both the levosimendan and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Tables II and III. The influence of heart rate on indices of transmitral flow found in this study are in agreement with those of others. 8,23,24 The positive influence of volume load (as measured by functional preload index or SVI) is noted on E wave, E TVI, A wave, and A TVI. This is in agreement with the findings of Stoddard et al 6 and Choong et al 20 Furthermore, contractility (measured as SVI) had a positive effect on E-wave amplitude, as expected from its tight association with excitation-contraction coupling.…”
Section: Present Studymentioning
confidence: 99%
“…3,4 Although Doppler-derived indices of diastolic function reflect changes in LV relaxation and compliance, interpretation of these changes is confounded by their codependency on heart rate, LV mass, systolic function, and loading conditions. [5][6][7][8] Previous studies showed that pregnancy has a profound effect on these variables 1, 2 which, in turn, are expected to influence mitral valve Doppler indices.…”
Section: Introductionmentioning
confidence: 99%